Qualidade de vida no pré e pós-implante de marca-passo em pacientes de um hospital público da região norte brasileira - Nunes, Genildo Ferreira (Universidade Federal do Tocantins, 2021)
Pacemakers (PM) have added new technologies in recent years, offering safety and reducing morbidity and mortality. However, in some cases, the quality of life (QoL) does not follow this result. Objective: To analyze the QoL of patients undergoing pacemaker implantation in the pre- and postoperative period at the Palmas General Hospital, Tocantins, Brazil. Methods: Quantitative, descriptive and prospective study, composed of 40 individuals undergoing PM implantation at the Palmas General Hospital. Three instruments were used for data collection: a clinical-sociodemographic questionnaire and the Medical Outcomes Study 36-Item Health Survey (SF-36) and the Assessment of QUAlity of life and RELated events (AQUAREL) quality of life questionnaires (before and after implantation). The Shapiro-Wilk (normality) and Wilcoxon tests were applied to compare QoL in the pre- and post-PM implantation, and the Mann-Whitney and Kruskal-Wallis tests to assess the association between variables, with a significance level of 5%. The research was approved by the Research Ethics Committee of the Foundation School of Public Health of Palmas under number 3,529,901. Results: The mean age was 69.8 ± 12.5 years; 52.5% were female; 60% knew how to read and write; 85% were retired and 10% lived alone. The period between collections was 83±20.3 days; the reason for implantation was sinus node disease in 25% of cases, atrioventricular block in 62.5% and others in 12.5%); 30% of patients were chagasic and 70% non-chagasic; 85% had dizziness, 82.5% tiredness, 52% palpitations and 32.5% syncopes; 90% received dual chamber and 10% single chamber PM, both conventional. The means of the SF-36 QoL domains before and after implantation, respectively, were: functional capacity 32.2±23 and 67.2±18.4; limitation due to physical aspects 12.5±21.1 and 76.8±29.6; pain 44.8±18.9 and 69.3±15.8; general health status 47.7±15.3 and 69.1±10; vitality 51.1±23 and 77.1±13.5; social aspects 61.5±24.7 and 79±19.6; emotional aspects 19.1±33.6 and 82.4±29.2; and mental health 64.1±18 and 75.4±15. The means of the AQUAREL domains were: chest discomfort 47.4±23.5 and 88.8±10.2; arrhythmias 57±14.9 and 95.1±5.8; and dyspnea on exercise 45.2±20.4 and 88.1±12.1. It was found that there was a significant difference between pre- and post-implantation for all QoL domains, in both instruments. In the post-implantation of PM, ventricular monochamber programming mode (VVI), atrial fibrillation, age over 70 years and illiteracy were associated with a positive effect on mental health (SF-36). Occupation and age ≤ 70 years were associated with a better response in the chest discomfort domain (AQUAREL). Conclusions: The PM implantation significantly improved the QoL of the evaluated patients. Schooling, occupation, age group, stimulation mode and electrocardiographic changes effected QoL.